Negative Emotions in Migraineurs Dreams: The Increased Prevalence of Oneiric Fear and Anguish, Unrelated to Mood Disorders. (23rd June 2014) - De Angeli, F.; Lovati, C.; Giani, L.; Mariotti D'Alessandro, C.; Raimondi, E.; Scaglione, V.; Castoldi, D.; Capiluppi, E.; Mariani, C.
Abstract : Background . Migraineurs brain has shown some functional peculiarities that reflect not only in phonophobia, and photophobia, but also in mood and sleep. Dreaming is a universal mental state characterized by hallucinatory features in which imagery, emotion, motor skills, and memory are created de novo. We evaluated dream contents and associated emotions in migraineurs. Materials and Methods . 412 subjects: 219 controls; and 148 migraineurs (66 with aura, MA; 82 without aura, MO), and 45 tension type headache patients (TTH). A semistructured retrospective self-reported questionnaire was used to evaluate dreams. The Generalized Anxiety Disorder Questionnaire (GAD-7), and the Patient Health Questionnaire (PHQ-9) were administered to evaluate anxiety and depression. Results . Migraineurs showed increased levels of anxiety (P = 0.0002 for MA versus controls, P = 0.004 for MO versus controls). Fear and anguish during dreaming were more frequently reported by migraine patients compared to controls, independently by anxiety and depression scores. Discussion . The brain of migraineurs seems to dream with some peculiar features, all with a negative connotation, as fear and anguish. It may be due to the recorded negative sensations induced by recurrent migraine pain, but it may just reflect a peculiar attitude of the mesolimbic structures of migraineurs brain, activated in both dreaming and migraine attacks.